Klotho Contributes to Pravastatin Effect on Suppressing IL-6 Production in Endothelial Cells - Weiwei Xia; Aihua Zhang; Zhanjun Jia; Jun Gu; Hongbing Chen (Hindawi Limited, 2016)
Both statins and klotho have been shown to be beneficial in vascular diseases. Interleukin- (IL-) 6 is evidenced as an indicator reflecting the stability of atherosclerotic plaque and involved in the pathogenesis of artery atherosclerosis. However, the relationship between statin, klotho, and IL-6 under an inflammatory environment is unknown. Using primary human umbilical vein endothelial cells (HUVECs), pravastatin dose-dependently induced klotho expression in contrast to remarkable suppression to IL-6 expressions determined by qRT-PCR. Moreover, TNF-α-induced IL-6 was partly but significantly blunted by pravastatin detected by ELISA. To further study the role of klotho in modulating IL-6 expression, endothelial cells with klotho overexpression were treated with TNF-α. Importantly, TNF-α-induced IL-6 production was markedly attenuated in klotho-overexpressed cells. In agreement with in vitro data, a marked reduction of klotho mRNA expression was found in isolated peripheral blood mononuclear cells (PBMCs) from patients with atherosclerosis. Together, these data suggested that pravastatin could suppress IL-6 production via promoting klotho expression in endothelial cells under inflammatory stimuli.